2001
DOI: 10.1053/joca.2000.0398
|View full text |Cite
|
Sign up to set email alerts
|

Morphological analysis of articular cartilage biopsies from a randomized, clinical study comparing the effects of 500–730kDa sodium hyaluronate (Hyalgan®) and methylprednisolone acetate on primary osteoarthritis of the knee

Abstract: These results cannot be explained simply by temporary restoration of the synovial fluid viscoelasticity, and provide further evidence that the specific fraction of hyaluronan used in this study is a useful tool in OA treatment, with a potential structure-modifying activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
0
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(80 citation statements)
references
References 24 publications
7
67
0
6
Order By: Relevance
“…This result has been confirmed by similar findings observed by Guidolin et al [10] who found that the number of viable chondrocytes in articular cartilage has significantly increased after hyaluronic acid (HA) treatment.…”
Section: Groupsupporting
confidence: 86%
See 2 more Smart Citations
“…This result has been confirmed by similar findings observed by Guidolin et al [10] who found that the number of viable chondrocytes in articular cartilage has significantly increased after hyaluronic acid (HA) treatment.…”
Section: Groupsupporting
confidence: 86%
“…into the left knee beginning 1 week after ACLT, once a week for 5 weeks. This schedule was the same as the current clinical application schedule of hyaluronic acid [10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…high-weight molecules contribute to form a high-viscosity solution, which serves as a lubricant and shock absorber [2,25], among other functions. Viscosupplementation reportedly relieves pain [13] but it also is considered a disease-modifying OA drug [14,29] with benefits that have been observed in a period of 6 months to 2 years [22]. It is believed that the long-term effectiveness of HA is attributable to its modulating action in the inflammatory process that occurs in the osteoarthritic joint and in its interaction with the CD44 synoviocytes receptors [28,30].…”
Section: Introductionmentioning
confidence: 99%
“…6 Intra articular injections of hyaluronic acid with a molecular weight between 500 and 750 kilodaltons (kD) have been studied using corticosteroid injections or NSAIDs as control treatment and by conducting placebo controlled trials. [7][8][9][10][11] These studies suggested that intra articular injections of HA may improve the clinical condition and have long term beneficial effect in knee osteoarthritis patients, if osteoarthritis is less than moderate in grade. A review by Maheu looked at 5 different clinical trials, comparing different regimens of Hyalgan versus corticosteroids injections in osteoarthritis knee, with follow ups from 2-12 mths.…”
Section: Introductionmentioning
confidence: 99%